Relative Dose Intensity of Induction-Phase Pazopanib Treatment of Soft Tissue Sarcoma: Its Relationship with Prognoses of Pazopanib Responders - Nakano, Kenji (J Clin Med, 2019)
The approved standard dose of pazopanib is 800 mg per day, but the appropriate dose of pazopanib to treat soft tissue sarcoma (STS) patients in real-world practice is controversial. Of 124 STS patients treated with pazopanib, we retrospectively analyzed the cases of STS patients who achieved progression-free survival at 12 weeks by pazopanib treatment as pazopanib responders, and we evaluated their relative dose intensity (RDI) in the initial 12 weeks (12W-RDI). We enrolled 78 STS patients in the analyses as pazopanib responders, and 54 patients of the 78 pazopanib responders (69%) were able to maintain 12W-RDI ≥80%. In landmark analyses, patients with 12W-RDI of 80% ≥80% had significantly longer progression-free survival compared to those with 12W-RDI <80% (30.7 weeks vs. 22.0 weeks, hazard ratio [HR]: 0.56 [95%CI: 0.33–0.94], p = 0.026). The most frequently observed reasons of treatment interruption and/or dose reduction of pazopanib during the initial 12 weeks were anorexia and liver function disorders. Liver toxicity was the adverse event most frequently observed in the 12W-RDI <80% patients throughout the treatment periods. Based on our results, it appears that maintaining as high a dose intensity as possible that is tolerable—at least during the initial 12 weeks—is likely to be the better option in pazopanib treatment for STS patients.